THE STUDENTS’ PERCEPTIONS OF READING HABITS, INTRAPERSONAL INTELLIGENCE, AND READING COMPREHENSION LEVELS - Rina Musliha; Amirullah Abduh; Muhammad Hasbi; Muh Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study was determined the students’ perceptions of reading habits, intrapersonal intelligence, and reading comprehension levels. The type of instrument in this study was questionnaire Researcher used quantitative method to collected the final scores of students’ perception. The sample of this study was showed to 30 students of the 12th - grade Language Class at Man 1 Bone from the language department who had English language skills was powerfull where the influence of reading habits and intrapersonal intelligence was related to their reading comprehension levels. All of the data in this study measured with SPSS 29 version for windows. Researcher had distributed the student perception questionnaire consisting of 15 statement items followed by 5 answer choices, namely Strongly Agree (SA), Agree (A), Neutral (N), Disagree (D) and Strongly (Disagree). Each statement had points used linkert scale ranging from point 5 to one which has been filled in by 30 students.. Based on the results of data analysis, researcher found that as many as 50% of students or 15 students out of 30 students were in the interval of 39-48 points with a cumulative score of 96.7%. So, they have quite well know about their abilities related to students' reading habits, intrapersonal intelligence, and reading comprehension levels. Therefore, the majority of students consider themselves to had good reading habits and intrapersonal intelligence that is in line with students' self-confidence the contents of texts